How to Build a Time‐Gated Luminescence Microscope. Issue 1 (16th February 2018) - Jin, Dayong; Lu, Yiqing; Leif, Robert C.; Yang, Sean; Rajendran, Megha; Miller, Lawrence W.
Abstract: The sensitivity of filter‐based fluorescence microscopy techniques is limited by autofluorescence background. Time‐gated detection is a practical way to suppress autofluorescence, enabling higher contrast and improved sensitivity. In the past few years, three groups of authors have demonstrated independent approaches to build robust versions of time‐gated luminescence microscopes. Three detailed, step‐by‐step protocols are provided here for modifying standard fluorescent microscopes to permit imaging time‐gated luminescence. Curr. Protoc. Cytom . 67:2.22.1‐2.22.36. © 2014 by John Wiley & Sons, Inc.